Physical activity and subjective well-being of older adults during COVID-19 prevention and control normalization: Mediating role of outdoor exercise environment and regulating role of exercise form - Yang, Qingqing; Tang, Yue; Jennings, George; Zhao, Bin; Zhu, Fusheng; Ma, Xiujie (Frontiers in Psychology, 2022)
Since the outbreak of the COVID-19 pandemic, the physical and mental health of older adults has been threatened. Promoting physical and mental health through physical activity has therefore become a strategy for healthy aging. In order to better understand the impact of the participation of older adults in physical activity, this paper selects different types of physical activity, and examines the relationship between them and subjective well-being through the analysis of the mediation effect of outdoor exercise environment and the regulating effect of exercise form. In this cross-sectional study, a questionnaire survey was conducted in mainland China. The main data come from 903 older adults in five urban areas in Chengdu, Sichuan Province. The surveys were carried out using the Physical Activity Rating Scale, Newfoundland Subjective Well-Being Scale, Exercise Environment Scale, and Exercise Form Scale. SPSS was used for statistical analysis, linear regression analysis was adopted for processing data, and AMOS was used to establish a mediation model. The mediating variable is the outdoor exercise environment, and the moderating variable is exercise form; gender, age, education level, and monthly income were used as control variables. The study results showed that different physical activities (tai chi; health qigong; walking and jogging) were significantly, positively correlated with the subjective well-being of older adults (tai chi: R = 0.351, p < 0.01; health qigong: R = 0.340, p < 0.01; walking and jogging: R = 0.245, p < 0.01); among the activities, tai chi had the strongest effect on the subjective well-being of older adults (R = 0.351, p < 0.01). Outdoor exercise environment played a mediating role between different physical activity types and subjective well-being of older adults [tai chi: β = 0.030, 95% CI (0.005, 0.031); health qigong: β = 0.018, 95% CI (0.000, 0.021); walking and jogging: β = 0.034, 95% CI (0.008, 0.035)]. Exercise form moderated the subjective well-being of older adults in different physical activities (tai chi: 0.006, p < 0.05; health qigong: 0.006, p < 0.05; walking and jogging: 0.009, p < 0.001). The results of this study demonstrate that the outdoor exercise environment plays a mediating role between different physical activities and the subjective well-being of older adults, and the form of exercise can also moderate the impact of different physical activities on the subjective well-being of older adults. This study has enlightening significance for psychological intervention with older adults facing stress, anxiety and depression.